Motivation i socialt arbete med försörjningsstöd - En kvalitativ studie om socialsekreterares upplevelser och erfarenheter - Andersson,Johan (2012)
The aim of the current study was to gain an overview of factors that can effect social secretaries motivation, both positively and negatively, in their work with social assistance. This study has focused on what the employee does rather than what he or she earns as a factor that leads to increased work motivation. To have motivated employees are important in every organization and above all in Human service organizations where the contact with clients is very close. This could then have an effect on the social secretaries sense of motivation and commitment in their work. To gain insight in a social secretaries experience of motivation semi- structured interviews have been carried out on six social secretaries in two different municipalities in Sweden. The interviews where then coded and categorized based on different motivational factors. The results showed important factors that had positive effect on social secretaries motivation. Some of them were, work results, making a difference, a feeling of contributing and the importance of a supportive manager who believes in you. Negative effects on motivations were factors such as clients with low motivation or clients with high demands. The difference in ambition between the client and the social secretary could even that have an impact on the social secretaries work and motivation. Interaction with people and the chance to be part of, and participate in change, was the primary motivational factor for the social secretaries in the current study.
Keywords: motivation; human service organizations; social assistance; social workers